STUDI PERSEPSI PENGUNJUNG TERHADAP PENGELOLAAN HUTAN DI KOTA MALABAR MALANG - Soleman Wadda Leba; Rizki Alfian; Hendra Kurniawan (Jurnal Lingkungan dan Kota, 2022)
Urban forest is one type of public green open space. Malabar City Fores is a protected area in Malang City. The purpose of the study was to identify visitors percepations of the management of the Malabar City Fores and to develop recommendations for ther management. The research methode used a questionnaire and observation. The area of the Malabar City Forest is 16,718 m2 and the number of trees is 1154, the forest has 79 species of trees and 22 species of birds. Visitors perceptions of the management of the Malabar City Forest based on the comfort aspec were 85.56% categoeized as very good, cleanliness 82.22% in good category. The recommendation for the management of the Malabar City Forest on the aspect of comfort is to provide education to the public about the importance of maintaining Green Open space. Recommendations for the management of the Malabar City Forest on the aspect of cleanliness int the redesign of the condition of the waste disposal system. While the recommenations for forest management in Malabar City on the aspect of facilities are revamping and improving the condition of the toilets so that they can comply with the standards of public toilets in Indonesia.